Epidemiology, burden, and attributable risks of infective endocarditis in Iran and its provinces: From 1990 to 2019. (15th September 2022) - Ajam, Ali; Shobeiri, Parnian; Keykhaei, Mohammad; Moghaddam, Sahar Saeedi; Momtazmanesh, Sara; Masinaei, Masoud; Esfahani, Zahra; Rezaei, Negar; Naderian, Mohammadreza; Aminorroaya, Arya; Rashidi, Mohammad-Mahdi; Rezaei, Nazila; et al.
Abstract: Background: Endocarditis is a potentially life-threatening infectious disease associated with significant morbidity and mortality and an escalating incidence in recent decades. In this study, as a part of the global burden of disease (GBD) 2019 study, we intend to report endocarditis burden in Iran at national and provincial levels from 1990 to 2019. Method: This study was conducted using GBD 2019 study data on endocarditis from 1990 to 2019. We gathered incidence, prevalence, disability-adjusted life years (DALYs), and mortality rates in Iran and its 31 provinces by sex and age groups as epidemiological indices for endocarditis burden. Further decomposition analysis was also performed to delineate the endocarditis new cases trend. Results: On the country scale, age-standardized incidence rate (ASIR), age-standardized prevalence rate (ASPR), age-standardized mortality rate (ASMR), and age-standardized DALYs rate were (16.5 (95% uncertainty interval 13.7 to 19.8), 3.4 (2.9 to 4.1), 0.6 (0.5 to 0.9), and 14.4 (12.0 to 21.1) in 2019, respectively. Decomposition analysis showed that only 59.2% of the overall new cases increase (114.1%) was caused by the incidence rate change. All estimated age-standardized rates were higher in men in 1990 and 2019 with a ratio of 1.1–1.5. Conclusion: The ASIR and ASPR of endocarditis increased, and the ASMR and age-standardized DALYs rate declined over the past 30 years in Iran, nearly all the provinces followed the same pattern with North Khorasan having the Highest ASIR, ASPR, ASMR, and DALYs rates in both years. High systolic blood pressure (SBP) had the greatest attributed burden among risk factors.